Role of CD4+CD25+FOXP3+ TReg cells on tumor immunity. Issue 2 (3rd April 2022) - Hariyanto, Agustinus Darmadi; Permata, Tiara Bunga Mayang; Gondhowiardjo, Soehartati Argadikoesoema
Abstract: Not all T cells are effector cells of the anti-tumor immune system. One of the subpopulations of CD4 + T cells that express CD25 + and the transcription factor FOXP3, known as Regulator T cells (TReg ), plays an essential role in maintaining tolerance and immune homeostasis preventing autoimmune diseases, minimalize chronic inflammatory diseases by enlisting various immunoregulatory mechanisms. The balance between effector T cells (Teff ) and regulator T cells is crucial in determining the outcome of an immune response. Regarding tumors, activation or expansion of TReg cells reduces anti-tumor immunity. TReg cells inhibit the activation of CD4 + and CD8 + T cells and suppress anti-tumor activity in the tumor microenvironment. In addition, TReg cells also promote tumor angiogenesis both directly and indirectly to ensure oxygen and nutrient transport to the tumor. There is accumulating evidence showing a positive result that removing or suppressing TReg cells increases anti-tumor immune response. However, depletion of TReg cells will cause autoimmunity. One strategy to improve or restore tumor immunity is targeted therapy on the dominant effector TReg cells in tumor tissue. Various molecules such as CTLA-4, CD4, CD25, GITR, PD-1, OX40, ICOS are in clinical trials to assess their role in attenuating TReg cells' function.